2013
DOI: 10.1249/mss.0b013e31828983f7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition Scores Associate with Muscular Strength, Size, and Trainability

Abstract: GPS for muscular phenotypes showed to be associated with baseline KES, muscle diameter, and the response to training in cardiac rehabilitation patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 40 publications
1
30
1
12
Order By: Relevance
“…The insignificance of age might be due to close ages of participants and limited training period. Although the findings of Thomaes' study 20 which did not find a significant relation between GPS and isometric knee extension strength, ANCOVA analysis in our study showed that GPS was positively related to baseline PTIM60. This might be attributed to a larger SNP pool in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The insignificance of age might be due to close ages of participants and limited training period. Although the findings of Thomaes' study 20 which did not find a significant relation between GPS and isometric knee extension strength, ANCOVA analysis in our study showed that GPS was positively related to baseline PTIM60. This might be attributed to a larger SNP pool in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Sibling and twin studies estimated the heritability of muscle strength and muscle mass, indicating that the individual genetic makeup can exert an influence on the development of muscle mass and strength 18 . This indicates that the response variability resulting from exercise might be related to inherited characteristics 19,20 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For instance, muscle maximal shortening velocity ( V max ) is positively correlated with fascicle length . Although no direct associations between TTN and fascicle length have been reported, the aforementioned C>T transition within the TTN gene has been identified as contributing significantly to a genetic predisposition for maximal isokinetic strength at 180°·s −1 but not 60°·s −1 , which could indirectly demonstrate that variability in V max is influenced by genotype‐dependent differences in fascicle length. Furthermore, enhanced efficiency of stretch‐shortening contractions can be expected in individuals possessing shorter muscle fascicles due to the lower metabolic cost of producing a given force.…”
Section: Introductionmentioning
confidence: 99%
“…Studies rely on these resources to obtain data related to the response to interventions related to exercise [18, 19]. Indeed, the possibility to identify genes and their allelic states that could determine which individuals would perform better in some sports disciplines brought the concept of genetic scores based on a personal genetic profile [20]. …”
Section: Commentmentioning
confidence: 99%